2016
DOI: 10.3346/jkms.2016.31.8.1262
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Functional Constipation in Young Children Attending Daycare Centers

Abstract: Our objective was to determine the risk factors associated with the development of functional constipation (FC) in young children attending daycare centers. A cross-sectional survey using a questionnaire based on the Rome III criteria was conducted in children aged 25 to 84 months from 3 randomly selected daycare centers in January 2016. The items in a questionnaire were statistically compared in the constipated and non-constipated groups. A total of 212 children were included and FC was found in 8.5%. Multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 13 publications
(12 reference statements)
9
55
0
Order By: Relevance
“…This finding agrees with that reported in other studies carried out in Colombia, (11) Korea (15) and USA (13) . However, it is not in line with other studies that showed gender predominance, in Southern India (10) , there was female predominance.…”
supporting
confidence: 83%
See 4 more Smart Citations
“…This finding agrees with that reported in other studies carried out in Colombia, (11) Korea (15) and USA (13) . However, it is not in line with other studies that showed gender predominance, in Southern India (10) , there was female predominance.…”
supporting
confidence: 83%
“…In the current study, mother's level of education was not significantly associated with functional constipation and this is agree with Minkyu Park et al's study (15) . Also, the numbers of siblings was not significantly associated with functional constipation which is the same as Minkyu Park et al's finding (15) .…”
supporting
confidence: 83%
See 3 more Smart Citations